Structural Correlation Pattern Mining for Large Graphs - Silva, Ariel; Meira Jr., Wagner (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2012: Anais do XXV Concurso de Teses e Dissertações, 2012)
How are personal interests related to the communities in large social networks? In order to answer this kind of question, we introduce structural correlation pattern mining, which is the identification of interesting associations between vertex attributes and dense subgraphs. We present a model and algorithms that explore search, pruning, sampling and parallelization strategies to solve this problem for large graphs. Results show that structural correlation pattern mining enables the discovery of relevant patterns in real-life datasets.